2017
DOI: 10.5999/aps.2017.01060
|View full text |Cite
|
Sign up to set email alerts
|

Cleft Lip and Palate Repair Using a Surgical Microscope

Abstract: BackgroundCleft lip and palate repair requires a deep and small surgical field and is usually performed by surgeons wearing surgical loupes. Surgeons with loupes can obtain a wider surgical view, although headlights are required for the deepest procedures. Surgical microscopes offer comfort and a clear and magnification-adjustable surgical site that can be shared with the whole team, including observers, and easily recorded to further the education of junior surgeons. Magnification adjustments are convenient f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“… 116 Multiple optical ports are open for adaptation of imaging devices such as video cameras or for assistants to share the identical FOV. 25 , 117 …”
Section: Technical Aspects Of Surgical Microscopementioning
confidence: 99%
See 3 more Smart Citations
“… 116 Multiple optical ports are open for adaptation of imaging devices such as video cameras or for assistants to share the identical FOV. 25 , 117 …”
Section: Technical Aspects Of Surgical Microscopementioning
confidence: 99%
“…In some procedures, meaningful assistance has to be given by a cosurgeon sharing the same view with surgical microscope. 25 , 117 , 190 It aids not only assistance but also teaching and participation of trainees. 25 The simplest way to share the identical surgical view is to use an optical splitter to split the light into two eyepieces.…”
Section: Technical Aspects Of Surgical Microscopementioning
confidence: 99%
See 2 more Smart Citations
“… 8 Kato et al also demonstrated advantages using the microscope during palatoplasty, with a significantly improved instrument handling and surgical site visualization when using the microscope. 9 In addition to these reasons, we believe that the improved optics also allows for a better teaching environment, notably the variable zoom, advantageous focal length of an operating microscope being between 450 mm and 600 mm, whereas loupes are usually <400 mm, and ability to capture photographs and record videos. Newer microscopes are being utilized that have 3D viewing in 4K that enhance the experience even more.…”
Section: Introductionmentioning
confidence: 99%